The borderles world: power and strategy in the interlinked economy - Ohmac, Kenichi (New York: Haper Perennial, 1991)
Contents: 1. An inside-out view of macroeconomics. 2. the equidistant manager. 3. getting back to strategy. 4. do more better. 5. the china mentallity. 6... getting rid of the headquarters mentality. 7. plating for a global harvest. 8. the global logic of strategic alliances. 9. lies, damned lies, end statistics. 10. develoment in a borderless world. 12. a steady hand.
Epilogue p. 211-215
Keywords: Developing Countries - Commerce - JaponDEVELOPING; Japan - Commerce - Developing Countries